Implementasi Manajemen Pendidikan Inklusi di PAUD Inklusi Saymara Kartasura - Mila Faila Shofa (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
This study attempts to describe the concept of inclusive education management in Early Childhood Education; to describe the implementation of inclusive education management in PAUD Inklusi Saymara Kartasura; to describe the implementation of inclusive education management in PAUD Inklusi Saymara. The method used is descriptive qualitative with research place in PAUD Inklusi Saymara Kartasura, Sukoharjo, Central Java. Data collection used observation, interview and documentation techniques on the implementation of inclusive education management, where the data validity checks used the source triangulation technique. The results of the study explain that inclusive education management in PAUD Inklusi Saymara is implemented in several stages: preparation of vision, mission and objectives of Early Childhood Education with inclusion setting, preparation of program of development and implementation of Inclusive education, Acceptance of students with inclusive setting, understanding the children with special needs, preparing Human Resources , preparing learning system and reporting of child development, Provision of facilities and infrastructures, cooperation with other parties, and monitoring and evaluation of early childhood education inclusion.